2017
DOI: 10.3390/nu9030269
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A2 Genotype Variations Do Not Modify the Benefits and Drawbacks of Caffeine during Exercise: A Pilot Study

Abstract: Previous investigations have determined that some individuals have minimal or even ergolytic performance effects after caffeine ingestion. The aim of this study was to analyze the influence of the genetic variations of the CYP1A2 gene on the performance enhancement effects of ingesting a moderate dose of caffeine. In a double-blind randomized experimental design, 21 healthy active participants (29.3 ± 7.7 years) ingested 3 mg of caffeine per kg of body mass or a placebo in testing sessions separated by one wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 39 publications
8
90
1
2
Order By: Relevance
“…In a recent study of 19 basketball players, acute ingestion of 3 mg/kg of caffeine produced similar effects on vertical jump performance in individuals with the AA genotype and AC/CC genotypes [11]. These results are in accord with a study that utilized a 30-s Wingate sprint test, while improvement in peak and mean power output was noted following caffeine ingestion, the researchers did not find differences in responses between genotypes [12]. Based on the results of these two studies, it seems variations in the CYP1A2 genotype may not affect the ergogenic effects of caffeine ingestion on high-intensity exercise performance.…”
Section: Introductionsupporting
confidence: 54%
“…In a recent study of 19 basketball players, acute ingestion of 3 mg/kg of caffeine produced similar effects on vertical jump performance in individuals with the AA genotype and AC/CC genotypes [11]. These results are in accord with a study that utilized a 30-s Wingate sprint test, while improvement in peak and mean power output was noted following caffeine ingestion, the researchers did not find differences in responses between genotypes [12]. Based on the results of these two studies, it seems variations in the CYP1A2 genotype may not affect the ergogenic effects of caffeine ingestion on high-intensity exercise performance.…”
Section: Introductionsupporting
confidence: 54%
“…However, although we were not able to conduct a comparison with similar studies in the sports branches under consideration, there are similarities in the literature in general. In other studies, in a comparison of the data related to the rs762551 polymorphism in endurance athletes, the results from the long-distance runners of our study group have strong similarities with the genotype data from the study of Soutward (2016) on athletes and the results of the study of Salinero et al (17).…”
Section: Distribution Of Cyp1a2 Gene Related To Caffeine Metabolism Isupporting
confidence: 81%
“…All these outcomes indicate that caffeine might be effective to increase performance in the 15‐s adapted version of the Wingate anaerobic test during the menstrual cycle. Measuring individual responses to caffeine should be conducted before caffeine is recommended as a substance to increase anaerobic performance in women, as it has been reported that some individuals do not positively respond to caffeine …”
Section: Discussionmentioning
confidence: 99%
“…Despite the initial controversy on this topic, the effectiveness of acute caffeine ingestion to improve peak and mean cycling power in the Wingate anaerobic performance test has been well established by recent investigations and meta‐analytic data . However, evidence also suggests that doses <3 mg of caffeine/kg of body mass or the use of coffee as the form caffeine administration might be less effective than the use of 3–9 mg/kg via pure anhydrous caffeine or caffeinated energy drinks . Caffeine ergogenicity for the Wingate test might persist with daily ingestion of 3 mg/kg of caffeine for 15–18 days; however, the magnitude of its ergogenic effect is higher the first day of ingestion, suggesting tolerance to this substance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation